Developing teaching kit on the use of micro-hydro generator in remote area - Megawati, Desak Made (Jurnal Inovasi Pendidikan IPA, 2017)
The study aimed at: (1) identifying the criteria of teaching kit feasibility for the advantages of micro-hydro generator in remote area; and (2) identifying the effectiveness of teaching kit implementation on the use of micro-hydro generator in remote area in order to improve the students? concept mastery on SMP Negeri 1 Rampi South Sulawesi. The study was a research and development that adapted the 4D model, which consisted of define, design, develop, and disseminate. The teaching kit that had been developed was a syllabus, lesson plans, student?s worksheet, and assessment instrument. For the data gathering, the researcher implemented the non-test technique, in the form of product validation sheet, student?s worksheet readability questionnaire sheet, teaching implementation sheet, and test technique, in the form of concept mastery test item sheet. The results of the study show that: (1) the teaching kit on the use of micro-hydro generator in remote area that has been developed falls into the ?Very Good? category for syllabus, lesson plan, and student?s worksheet; and (2) the implementation of the teaching kit on the use of micro-hydro generator in remote area has been effective to improve the students? concept mastery in SMP Negeri 1 Rampi South Sulawesi.